Troubled in the land of enchantment adolescent experience of psychiatric treatment - Jenkins, Janis H.; Csordas, Thomas J. (University of California Press, 2020)
"In this groundbreaking study based on five years of in-depth ethnographic and interdisciplinary research, Troubled in the Land of Enchantment explores the well-being of adolescents hospitalized for psychiatric care in New Mexico. Anthropologists Janis H. Jenkins and Thomas J. Csordas present a gripping picture of psychic distress, familial turmoil, and treatment under the regime of managed care that dominates the mental health care system. The authors make the case for the centrality of struggle in the lives of youth across an array of extraordinary conditions, characterized by personal anguish and structural violence. Critical to the analysis is the cultural phenomenology of existence disclosed through shifting narrative accounts by youth and their families as they grapple with psychiatric diagnosis, poverty, misogyny, and stigma in their trajectories through multiple forms of harm and sites of care. Jenkins and Csordas compellingly direct our attention to the conjunction of lived experience, institutional power, and the very possibility of having a life"--